Pembelajaran Mengidentifikasi Unsur Komplikasi Dalam Cerita Pendek Dengan Model Discovery Learning Berorientasi Pada Peningkatan Kemampuan Berkolaborasi Peserta Didik Kelas XI SMA Negeri 3 Cimahi Tahun Pelajaran 2022/2023 - Ai Rusmiyati; Titin Nurhayatin; Musaddad Abdul Azis (Lembaga Pengembangan Kinerja Dosen, 2023)
This research is motivated by the low ability of students to identify complications in short stories. The lack of variety of learning models used by educators is one of the causes. The selection of various learning models will greatly influence the process of learning activities so that they become active, creative and innovative in order to improve the quality of students. One learning model that is effectively used is Discovery Learning. In addition, the low ability to collaborate is also due to the lack of assignments given in groups by educators to students. The purpose of this study was to examine the effectiveness of the Discovery Learning model used in increasing the ability to identify complications in short stories and to improve students' collaboration skills. In addition, this study aims to examine differences in the ability to identify complications in short stories and the ability to collaborate between the experimental class using the Discovery Learning model and the control class using the discussion method. The method used is a quasi-experimental method with nonequivalent control group design. The results obtained based on the Wilcoxon test are the Asymp values. Sig. (2-tailed) <.001 or 0.001 <0.05, it can be concluded that there is a difference between students' learning outcomes in identifying complications in short stories between the experimental class using the Discovery Learning model and the control class using the discussion method. The results obtained based on the Mann Whitney-U test are the Asymp values. Sig. (2-tailed) of 0.010 <0.05, meaning that the Discovery Learning model is effectively used in learning. The value of collaborating in the experimental class has an average (mean) of 3.61 and the control class has an average (mean) of 3.47, meaning Discovery Learning model that it is very effective in improving collaboration skills.